Evolution of a Geriatric Syndrome: Pathophysiology and Treatment of Heart Failure with Preserved Ejection Fraction. Issue 11 (10th November 2017) - Upadhya, Bharathi; Pisani, Barbara; Kitzman, Dalane W.
Abstract : The majority of older adults who develop heart failure (HF), particularly older women, have a preserved left ventricular ejection fraction (HFpEF). The prevalence of this syndrome is increasing, and the prognosis is not improving, unlike that of HF with reduced ejection fraction (HFrEF). Individuals with HFpEF have severe symptoms of effort intolerance, poor quality of life, frequent hospitalizations, and greater likelihood of death. Despite the importance of HFpEF, there are numerous major gaps in our understanding of its pathophysiology and management. Although it was originally viewed as a disorder due solely to abnormalities in left ventricular diastolic function, our understanding has evolved such that HFpEF is now understood as a systemic syndrome involving multiple organ systems, and it is likely that it is triggered by inflammation and other as‐yet‐unidentified circulating factors, with important contributions of aging and multiple comorbidities, features generally typical of other geriatric syndromes. We present an update on the pathophysiology, diagnosis, management, and future directions in this disorder in older persons.